Industry and commerce tax in the city of Bogotá Capital District, importance and inclusion to the simple tax regime (2020)
In the current reality, it is imperative that some State policies are analysed, with the purpose of obtaining more information about the management that the national government can give to the resources that it will receive temporarily from district and territorial entities, the one that concerns us in this sense is the Industry and Commerce Tax, the most rewarding for the capital, as it is described in the data of the Management Report 2019, of the District Secretary of Finance; Hence, some sections of the evolutionary advance of taxation, the attributes of the ICA, the regulations, the percentage participation and in the same way, the immersion in the Unified Tax of the RST is partially analysed. It should be indicated that for the great philosophers of history such as Aristotle, who in his book "Politics" affirmed: "There are also States that in times of adversity, have resorted to this jurisdiction, attributing to themselves the general monopoly of all sales" (Aristotle, 2009), A currently reveal is needing to obtain funds with the Financing Law, which are being researched by all means to procure it, that is, paradoxically, the Capital District is part of that purpose.